Students’ Learning Styles in Higher Education - Hermini Hermini; Rahmawati Upa; Edi Wahyono (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This research aims to find the dominant students’ learning style and their opinion about online class. It is descriptive study. 42 students were taken as sample by purposive sampling technique for they have online class during COVID-19. This result show that the most dominant learning style is visual learning style (78.4%). And they mostly have negative opinion about online class. (75.6%) of the students do not like it and (78.04%) are not motivated on online class. The most dominant reason is that it is hard to understand the instruction and material. Besides that, they feel that online classroom does not accord to their learning styles (85.36%). Somehow, 95.12% of the students were active on online class and 21.9% are motivated for students feel free/not ashamed in online class than in real class. So most of the students are visual learner and most of them have negative perspective toward online class.